Polymers in ophthalmic preparations: from traditional application to product innovation - Krajišnik, Danina (Archives of Pharmacy, 2022)
Drug delivery to the eye is still one of the most important areas of modern ocular therapy, since it encompasses many opportunities and challenges. Traditional use of polymers (both natural and synthetic) as excipients in ophthalmic preparations provides better bioavailability by drug stabilization, viscosity increasing, mucoadhesion and retained elimination rate from the eye, which reduces the frequency of drug administration and enhances patient compliance. Furthermore, some polymers have properties of ocular penetration enhancers or enable the formation of in situ gels in contact with various physiological stimuli (ions, pH or temperature). The versatility of biopolymers and synthetic polymers have been applied for formulation of various micro- and nanocarriers (e.g., microparticles, microneedles, nanoparticles, nanocapsules, polymeric micelles, dendrimers, and liposomes) which demonstrate significant potential for treatment of ocular diseases in both anterior and posterior segment of the eye. Processing polymers into fibers, films, contact lenses, or extruded forms allows design of specifically engineered devices enabling accuracy of dosing, prolonged drug release, chemical stability, and absence of preservatives. Although significant effort has been devoted to development of polymer-based ocular drug delivery systems, a key challenge is still the translation of these systems to clinical use. Biocompatibility is an essential property for all ocular drug delivery systems since their components should not interact with the surrounding tissue or elicit foreign body reactions through inflammatory or immune response. Overall, despite numerous challenges, further investigative research emerging innovative applications of polymeric materials in ocular drug delivery is expected in the near future.